The Influence Of Leadership Transformation, Work Motivation, And Job Satisfaction On Employee Performance Through Work Discipline - Sendi Cendiawan; Rhian Indradewa (LPPM Universitas Respati Indonesia, 2024)
The ability of an organization to survive and develop properly is determined by the competence of the human resources owned by the organization through various variables that can influence it, such as transformational leadership, work motivation, job satisfaction, and work discipline. This study used a quantitative method by distributing questionnaires to respondents, totaling 170 employees at the Tanjung Priok Class I Port Health Office. Data were analyzed using the PLS Structural Equation Model (SEM). Some of the findings in this study are that transformational leadership does not affect work discipline and employee performance, work motivation has a negative effect on work discipline and employee performance, job satisfaction has a positive effect on work discipline and employee performance, and work discipline has a positive effect on employee performance. Furthermore, it is demonstrated in this study that work discipline can mediate the effects of work motivation and job satisfaction on employee performance. Keywords: Transformational leadership, work motivation, job satisfaction, work discipline, and employee performance